Insights into the specialty mushrooms production in China - Key takeaways to Indian farmers - ANNEPU, SUDHEER KUMAR; Gupta, Sachin (Mushroom Research, 2021)
Mushroom farming in India is now a new way of farming to create circular economy and for doubling the farmers’ income. In the last two decades, the research efforts of ICAR-DMR, Solan in collaboration with the research centers under AICRP on mushrooms have contributed significantly to the growth of Indian mushroom industry and standardized several composting and cultivation technologies for different mushrooms. It resulted in significant increase in mushroom production in India from 0.05 million MT in 2000-01 to 0.23 million MT by the year 2020-21. However, mushroom production and consumption in India is still inadequate in comparison to the global trends. Though mushrooms have been aggressively promoted as the super food with many therapeutic benefits, the production of medicinal mushrooms and other specialty mushrooms have not reached to the noticeable level in India. On the other side, China which is the leading global producer and supplier of mushrooms in the world is producing more volume of specialty and medicinal mushrooms and reaching every corner of the globe with its low cost and quality mushroom products. In this paper, we made a comprehensive attempt to describe the production systems in specialty mushrooms for the benefit of Indian mushroom growers. The paper is based on the learning experiences from the International Training Workshop on Edible and Medicinal Mushrooms organized by the Shanghai Academy of Agricultural Sciences, China P.R. The insights presented here will be useful for diversification of the Indian mushroom industry and will also provide a road map for a thoughtful policy intervention to tap the potentiality in mushroom farming.